Strategi Gereja Dalam Membangun Persekutuan Umat Allah - Karolina Suwul; Intansakti Pius X (Jurnal Magistra, 2024)
Etymologically, the Greek Church “Ekklesia” means “ called out”. The Churh is often also defined as “a community of believers” (Andreas, 2010, p. 21). The Church is living community of everyone. The Church is a community formed by Christ, intended to illuminate the word to become His salt. The Church is also a collection of believers who believe in Christ as the head of the Church. The pastor in a Church is the hope or foundation for all members of the congregation, with a great influence on the dynamics and success of the congregation. The Church must have a friendly attitude and embrace all individuals. Judging from its journey, the Church is similar to the attitude of Jesus who welcomed everyone regardless of their status or background. It is necessary to build a community that makes a pilgrimage together to achieve the common goal of building a communion Church, the Church is the people of God, the Church needs to embrace all in brotherhood. Thus the Church is a communion (Communio). Communion in scripture is something very special and broad in the view of Christians. Fellowship is the basis of life from God, the faith of every Christian teaches the infinite unity of God. This view is on a biblical basis, in the Old and New Testaments. The from of the Church of God’s people is the fruit of reflection on salvation history. This reflecation is the fellowship of the Old Testament people.